Fear of Falling and Visual Field Loss from Glaucoma - Ramulu, Pradeep Y. (2012)
OBJECTIVE: To determine if visual field (VF) loss from glaucoma is associated with greater fear of falling. DESIGN: Prospective observational study. PARTICIPANTS: Fear of falling was compared between 83 glaucoma subjects with bilateral VF loss, and 60 control subjects with good visual acuity and without significant VF loss recruited from patients followed for suspicion of glaucoma. METHODS: Participants completed the University of Illinois at Chicago Fear of Falling Questionnaire. The extent of fear of falling was assessed using Rasch analysis. MAIN OUTCOME MEASURES: Subject ability to perform tasks without fear of falling was expressed in logits, with lower scores implying less ability and greater fear of falling. RESULTS: Glaucoma subjects had greater VF loss than control subjects (median better-eye mean deviation (MD) of −8.0 decibels [dB] vs. +0.2 dB, p<0.001), but did not differ with regards to age, race, gender, employment status, the presence of other adults in the home, body mass index (BMI), grip strength, cognitive ability, mood, or comorbid illness (p≥0.1 for all). In multivariable models, glaucoma subjects reported greater fear of falling as compared to controls (β= −1.20 logits; 95% Confidence Interval [CI] = −1.87 to −0.53; p=0.001), and fear of falling increased with greater VF loss severity (β= −0.52 logits per 5 dB decrement in the better eye VF MD; 95% CI = −0.72 to −0.33; p<0.001). Other variables predicting greater fear of falling included female gender (β= −0.55 logits; 95% CI = −1.03 to −0.06; p=0.03), higher BMI (β= −0.07 logits per 1 unit increase in BMI; 95% CI = −0.13 to −0.01; p=0.02), living with another adult (β= −1.16 logits; 95% CI = −0.34 to −1.99 logits; p=0.006), and greater comorbid illness (β= −0.53 logits/1 additional illness; 95% CI = −0.74 to −0.32; p<0.001). CONCLUSIONS: Bilateral VF loss from glaucoma is associated with greater fear of falling, with an impact that exceeds numerous other risk factors. Given the physical and psychological repercussions associated with fear of falling, significant quality of life improvements may be achievable in patients with VF loss by screening for, and developing interventions to minimize, fear of falling.